THE ANALYSIS OF STUDENTS` PERCEPTION ON THE USE OF WHATSAPP GROUP (WAG) AS MEDIA IN LEARNING WRITING DURING PANDEMIC ERA - Liafdinal, Ega Oktafia; Handayani, Fitri; Sepyanda, Marsika (IdeBahasa, 2023)
This research aimed to know the students` perception of the use of WhatsApp group (WAG) as media in learning writing at the ninth grade of SMPN 3 Solok in the 2021/2022 academic year. This research was conducted by using quantitative descriptive research was used as the design for this research. In collecting data, questionnaire was used as the instrument of the research in collecting the data given to the students. In this case the researcher used 30 number of statements which based on 3 aspect of students` perception. The aspects of perception were divided into cognitive, affective, and psychomotor aspects. The finding of the research can be concluded that students` perception on the use of WhatsApp group as media in learning writing during pandemic era at the ninth grade students` of SMP 3 Solok at 20021/2022 academic year was in the “Good” level. It can be seen from students` positive responses in responding the questionnaire given about the use of WhatsApp groups in learning to write during the pandemic. Through this research, teachers are advised to encourage students to use WhatsApp groups in learning to write during pandemic because based on the research that has been done, WhatsApp groups have had a good impact and response from students in learning, especially in writing activities.